A Proposed Link Between Acute Thymic Involution and Late Adverse Effects of Chemotherapy - Lagou, Maria K.; Anastasiadou, Dimitra P.; Karagiannis, George S. (Frontiers in Immunology, 2022)
Epidemiologic data suggest that cancer survivors tend to develop a protuberant number of ad-verse late effects, including second primary malignancies (SPM), mainly due to the treatment with cytotoxic chemotherapy. Besides the genotoxic potential of these drugs that directly inflict mutational burden on genomic DNA, the precise mechanisms contributing to SPM development are poorly understood. Cancer is nowadays perceived as a complex process that goes beyond the concept of a genetic disease and includes tumor cell interactions with complex stromal and immune cell microenvironments. The cancer immunoediting theory in particular offers an attractive explanation for the development of nascent neoplastic cells. Briefly, the cancer immunoediting theory suggests that newly emerging tumor cells are mostly eliminated by an effective tissue immunosurveillance, but certain tumor variants may occasionally escape innate and adaptive mechanisms of immunological destruction, entering an equilibrium phase, where immunologic tumor cell death “equals” new tumor cell birth. Subsequent microenvironmental pressures and accumulation of helpful mutations in certain variants may lead to an escape from the equilibrium phase, and eventually cause an overt neoplasm. The cancer immunoediting process functions as a dedicated sentinel under the auspice of a highly competent immune system. This perspective offers the fresh insight that chemotherapy-induced thymic involution, which is characterized by the extensive obliteration of the sensitive thymic epithelial cell (TEC) compartment, can cause long-term defects in thymopoiesis and in establishment of diverse T cell receptor repertoires and peripheral T cell pools of cancer survivors. Such delayed recovery of the T cell adaptive immunity may result in the prolonged hijacking/disturbance of the cancer immunoediting mechanisms, and lead to the development of persistent and mortal infections, inflammatory dis-orders, autoimmune precursor lesions, and SPMs. Acknowledging that chemotherapy-induced thymic involution could be a potential risk factor for the emergence of SPM demarcates new avenues for the rationalized development of pharmacologic interventions to promote thymic re-generation in patients receiving cytoreductive chemotherapies.